Costo-efficacia dell’amfotericina B liposomiale nella terapia dell’aspergillosi invasiva - Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2004)
Invasive aspergillosis (IA) is a common and life-threatening infectious complication of immune system depression. Amphotericin B deoxycholate (AMB-d) has been considered standard therapy for IA for over 40 years, despite the fact that success rates rarely exceed 40% and adverse effects are quite common. At present two more recent pharmacological agents are available for the treatment of IA: liposomal amphotericin B (L-AMB) and voriconazole (VOR). In this article, we present a pharmaco-economical study comparing the relative costeffectiveness of 5 alternative strategies in the treatment of invasive aspergillosis, analysed from the point of view of the Italian hospital: administration of L-AMB as first line therapy, followed by no rescue treatment in case of failure (L-AMB I°); administration of L-AMB as first line therapy, followed by VOR in case of failure (LAMB I° + VOR rescue); AMB-d as first line, followed by L-AMB in case of failure (L-AMB rescue); AMB-d as first line, followed by other antifungals as needed (AMB-d I°) and VOR as first line, followed by rescue treatments in case of failure (VOR I°). The cost-effectiveness analysis was conducted using decision tree modelling techniques: efficacy data were obtained from published clinical trials; costs parameters were fitted on the Italian setting. The results indicate that two strategies, L-AMB rescue and VOR I°, are dominated, i.e. induce higher costs and lower success rates than the alternatives. The three remaining strategies are neither dominated nor dominate the others, but are associated with different clinical and economical outcomes: AMB-d I° has the lowest total cost, but also the highest cost-effectiveness ratio and the lowest overall efficacy; L-AMB I° has the best cost-effectiveness, but requires the willingness to pay 2,100 euro for each additional success; L-AMB I° + VOR rescue is the most effective treatment, but this choice is associated with incremental costs of 17,200 euro for each additional success, compared with L-AMB I°. In conclusion, our analysis indicates that for clinical, economical and ethical reasons the best option in the treatment of IA is the administration of L-AMB as first line therapy, thus limiting the use of VOR to the rescue of the patients not cured by this approach.